The Scope of Public Services Performed by Municipal Local Governments in the Republic of Poland Through Budgetary Establishments - Ofiarska, Małgorzata (Public Governance, Administration and Finances Law Review, 2018)
The Act of 27 August 2009 on public finance – which entered into force on 1 January 2010 – and its later amendments have brought about significant changes in the scope of public services performed by the commune’s self-governments through budgetary establishments. The key change has been the limitation of these services, which triggered the necessity to implement new organizational methods and new financing solutions for public services hitherto carried out by budgetary establishments. Local government authorities were forced to choose between three organizational forms and three different ways of financing of the said services. At present, public services in a commune can be carried out through: a budgetary unit (a form most closely linked to the commune’s budget), a budgetary establishment (a form indirectly linked to the commune’s budget) and a municipal corporation (a form that in fact assumes full commercialization of public services). The aim of the paper is to analyse and evaluate relevant legislation, judicial practice of courts and regional accounting chambers, as well as the doctrine of local government law and public finance law regarding the scope of public services that can be financed through budgetary establishments. The hypothesis that the legislator’s implementation of new legal regulations since 2010 has led to implementation of more effective management methods with regard to public services and management of public finance allocated to these services was proven to be right. The legislator’s act of giving local government authorities relative freedom as to the choice of organizational and legal forms through which public services will be performed is tantamount to expecting that the authorities shall perform their tasks rationally. The leading method applied in the paper was the dogmatic and legal method, supported by the empirical and analytical method (in particular with regard to the judicial practice of courts and regional accounting chambers).